Dynamical evolution of Inner-Earth objects (IEO) - Di Sisto, Romina Paula (2025)
Inner-Earth objects are a subgroup of near-Earth objects (NEOs) whose orbits are entirely contained within Earth's orbit. Within this group, Atira asteroids have aphelion distances (Q) in the range 0.718AU < Q < 0.983AU, Vatiras have orbits completely interior to Venus (0.307AU < Q < 0.718AU), and Vulcanoids are hypothesized to have orbits interior to Mercury. Very few of these objects have been discovered due to their proximity to the Sun, which makes observation challenging. In this study, we investigate the dynamical evolution of the observed Atira and Vatira asteroids (no Vulcanoids have been observed to date) using numerical simulations, building upon the initial work of [1].